Biotechnology research applied to cassava improvement at the International Center of Tropical Agriculture (CIAT) - Roca, W.; Henry, Guy; Angel, F.; Sarria, R. (International Center for Tropical Agriculture, 1992)
CIAT activities in developing biotechnology applications to cassava in the last decade are described. The strategies to identify research topics and implement in house capabilities and an international cooperative effort in cassava biotechnology are emphasized. Successful integration of selected biotechniques into the research on cassava germplasm conservation, characterization, and propagation at CIAT and national programs in developing countries is highlighted, and progress in developing advanced biotechnology tools for genetic mapping and manipulation at CIAT is presented. The CIAT efforts are oriented to link modern biological research with the needs of cassava farmers through the generation of low input, environmentally friendly, germplasm-based technologies. (AS)